Absolute Configuration of Eight Cephalimysins Isolated from the Marine‐Derived Aspergillus fumigatus. Issue 33 (29th November 2017) - Yamada, Takeshi; Kimura, Hiroyuki; Arimitsu, Kenji; Kajimoto, Tetsuya; Kikuchi, Takashi; Tanaka, Reiko
Abstract: Eight new metabolites with spiro‐heterocyclic γ‐lactam cores, cephalimysins E–L, were isolated from a culture broth of Aspergillus fumigatus that was originally separated from the marine fish Mugil cephalus . In spite of the presence of six chiral centers in cephalimysins E–L, no other diastereomers of them were isolated from the natural source except for eight unnatural forms that could be obtained by treating cephalimysins E–L with acidic methanol. The occurrence of cephalimysins E–L was rationalized via molecular energy calculations by assuming that these isomers were derived from annelation of a spiro‐heterocyclic γ‐lactam with an E‐ olefin on the side chain such as the E‐ isomer of pseurotin A. Biosynthetic consideration of the metabolites based on molecular orbital calculations demonstrated that the 16 stereoisomers can all exist, and their stereochemistry was unambiguously determined using circular dichroism spectra, nuclear Overhauser effect spectroscopy, and two‐dimensional nuclear magnetic resonance spectra. Abstract : Eight new spiro‐heterocyclic γ‐lactams designated as cephalimysins E–L (1 –8 ) were isolated from a marine fish‐derived fungus, A. fumigatus . Treatment of the compounds with acidic methanol gave a set of eight unnatural forms (1'–8'), providing 16 stereoisomers. The stereochemistry of them considered by the examination using molecular orbital calculations. In the CD spectra, symmetrical Cotton effects between enantiomers reflect the above results.